Understanding the Linux kernel - Bovet, Daniel P. (Daniel Pierre) (O'Reilly, 2001)
Explains the operating system's hidden processes, covering memory management, the Virtual File System, process creation and scheduling, signals, essential interfaces, timing, and synchronization in the kernel.